Pengaruh Product Diversity, Price Perception, Location, dan Service Quality terhadap Repurchase Intention Konsumen Kopi Njongke Yogyakarta - Nurul Offia Fatimah; Ralina Transistari (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2022)
This study aims to analyze the effect of product diversity, price perception, location, and service quality on repurchase intention of Kopi Njongke Yogyakarta consumers. The sampling technique used purposive sampling method. Data was obtained by distributing questionnaires to 121 respondents. Data analysis was performed using multiple linear regression method. Before the regression was carried out, the instrument was tested, namely the validity and reliability test, the basic assumption test was the normality test, the classical assumption test which included the multicollinearity test and the heteroscedasticity test. and data analysis using f test (Goodness of Fit), t test, and coefficient of determination. The results showed that there was no significant effect of product diversity and location on repurchase intention, while price perception and service quality had a positive effect on repurchase intention. The coefficient of determination of the results of this study was 0.550, indicating that the product diversity, price perception, location, and service quality variables contributed 55% to the repurchase intention variable. The results of this study can enrich references related to the variables studied and can also be a consideration for businesses in the culinary field to increase consumer repurchase intention.